Pollution produced by intensive fish farming in Andean lagoons, Junín, Peru - Mariano, Mauro (2010)
We report the changes produced by intensive farming of rainbow trout Oncorhynchus mykiss in seven Andean lagoons. The observations were made in 1996 and between 2002-2007 and allowed to observe the deterioration of the lakes, characterized by the increase in total phosphorus concentrations and decreased dissolved oxygen and transparency. The benthic community was evaluated in seven lakes in 2007, resulting low number of species and diversity indices (H `<1,26; <8 spp.). The abundance ranged from 7 to 35 ind. /0,04 m2. Organic matter and carbonates were high in the bottom (from 30,22 to 42,45%).